Characterization of races of Xanthomonas campestris pv. malvacearum with SDS-PAGE and DNA restriction fragment analysis - Vivier, Melané Alethea (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.